Kuantifikasi Kadmium (Cd) dan Kromium (Cr) dalam Kerang Bakalang (Marcia Hiantina) di Perairan Selat Makassar (Window of Public Health Journal, 2026)
The coastal areas of the Makassar Strait are rich in fishery resources, one of which is the bakalang shellfish. However, this area is at risk of pollution due to complex activities, such as industrial, fishery, port, and household activities, which are factors that contribute to pollution. This study aims to determine the environmental health risks due to cadmium (Cd) and chromium (Cr) content in bakalang clams (Marcia Hiantina) in the waters of Lantebung Bira, Makassar City, in 2025. The type of research used is descriptive observational. Samples were taken at six points, with one sample taken at each point using selected sampling, considering the level of pollution in the area that could cause Cd and Cr to be present in the waters. The tools used were a knife, scales, measuring flask, filter paper, porcelain dish, and AAS equipment, while the materials used were clam meat, distilled water, and HNO3. The results of heavy metal content testing in shellfish showed that out of six locations, only one location had chromium (Cr) levels exceeding the maximum limit set by the Hong Kong Food Adulteration (Metallic Contamination) Ordinance 1997, indicating potential pollution from various human activities such as shipping lanes, industrial waste, settlements, and the use of anti-rust paint and marine lubricants. Meanwhile, cadmium (Cd) levels at all points were still below safe limits, but caution is still warranted given the accumulative nature of Cd in biota tissue.